2005
DOI: 10.1016/j.lungcan.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the third-generation bisphosphonate, zoledronic acid alone and combined with anti-cancer agents against small cell lung cancer cell lines

Abstract: Small cell lung cancer (SCLC) is one of the most aggressive types of cancers because of its early development of regional and distant metastases. Novel and more effective therapeutic strategies for the treatment of this disease are necessary. Bisphosphonates (BP), originally developed to treat bone disease, have recently been identified as attractive cancer theraptic agents. In this study, we investigated the anti-proliferative effects of zoledronic acid (ZOL) as a single agent and in combination with other ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
94
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 31 publications
11
94
1
Order By: Relevance
“…YM529 demonstrated good synergistic or additive antiproliferative effects when administered in combination with cisplatin or paclitaxel on three human bladder cancer cell lines (Table 2). These results are consistent with many other studies against a range of tumour cell lines (Jagdev et al, 2001;Kimura et al, 2004;Matsumoto et al, 2005). We speculate that addition of BPs to existing chemotherapeutic regimens, as exemplified by MVAC plus ZOL therapy, might improve the effectiveness of the treatment.…”
Section: Discussionsupporting
confidence: 92%
“…YM529 demonstrated good synergistic or additive antiproliferative effects when administered in combination with cisplatin or paclitaxel on three human bladder cancer cell lines (Table 2). These results are consistent with many other studies against a range of tumour cell lines (Jagdev et al, 2001;Kimura et al, 2004;Matsumoto et al, 2005). We speculate that addition of BPs to existing chemotherapeutic regimens, as exemplified by MVAC plus ZOL therapy, might improve the effectiveness of the treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we examine the combined effects of ZOL with commonly used anti-osteosarcoma agents such as DOX, CDDP and MTX. CDDP has been reported to augment synergistically the effects of ZOL (Matsumoto et al, 2005). We also examine the combined effects of ZOL with other three agents that are undergoing clinical trial or have been examined in vitro experiments for osteosarcoma cells, such as IM (McGary et al, 2002), PAC (Verweij et al, 2000) and GEM (Okuno et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that third-generation BPs such as zoledronic acid (ZOL) and minodronic acid YM529 show direct antitumour effects and synergistically augments the effects of anticancer agents in various cancer cell lines (Kuroda et al, 2003;Kimura et al, 2004;Matsumoto et al, 2005;Segawa et al, 2005;Yuasa et al, 2005). Recently, several investigators have reported the antiosteosarcoma effects of third-generation BPs in vitro (Evdokiou et al, 2003;Kubista et al, 2006;Kubo et al, 2006;Tenta et al, 2006) and in vivo Ory et al, 2005).…”
mentioning
confidence: 99%
“…As evidenced for bone metastasis, a vicious cycle between osteoclasts, stromal cells/ osteoblasts, and cancer cells has been hypothesized during the progression of primary bone tumors (Chirgwin and Guise, 2000). Bisphosphonates are currently used in the treatment as well as in co-adjuvant therapy for these pathologies (Horie et al, 2006;Jagdev et al, 2001;Matsumoto et al, 2005) because they have a high affinity for the hydroxyapatite mineral in bone and are taken up selectively and adsorbed to mineral surfaces at sites of increased bone turnover where they inhibit osteoclast activity (Kellinsalmi et al, 2005;Rodan and Fleisch, 1996). Moreover, bisphosphonates can inhibit the development and viability of mature osteoclasts and in addition, they may exert their actions indirectly by affecting neoplastic cells (Evdokiou et al, 2003;Heymann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%